An Overview of Islam and Religious Moderation: Concept, Principles, and Indicators - Kusmidi, Henderi (UIN Fatmawati Sukarno Bengkulu, 2022)
This article discusses the concept, principles and indicators of religious moderation following the al-Qur'an and Hadith. Qualitative with a literature approach is the method of choice in this article. This study conveys the concept of religious moderation in Islam as an effort to direct Muslims to be the best with indicators of noble character, helping each other, respecting the views of others, spreading goodness and justice, having noble character, not blaspheming and demeaning each other, not blaming each other, and not feeling most correct. Then, the values of religious moderation are found in Q.S al-Baqarah verse 143: 1) Tawassuth is an attitude that is not extreme, practising religious teachings without reducing or exaggerating, and not taking sides or leaning towards one group; 2) Tawazun is an effort to balance life for the world and the hereafter; 3) I'tidal can be interpreted as an effort to be a just human being in various matters for peace and not taking sides with anyone.